2008
DOI: 10.1021/ja8073006
|View full text |Cite
|
Sign up to set email alerts
|

Three Component Coupling of α-Iminoesters via Umpolung Addition of Organometals: Synthesis of α,α-Disubstituted α-Amino Acids

Abstract: The synthesis of alpha,alpha-disubstituted alpha-amino acids by means of a three component coupling is reported. The coupling occurs through umpolung addition of organometallic reagents to the nitrogen of alpha-iminoesters. The resulting enolate intermediates subsequently react with electrophiles (aldehydes, imines, alpha,beta-unsaturated nitro, alkyl halides, acyl cyanides) to form a quaternary center. Tethering of the electrophile and nucleophile components provides cyclic alpha,alpha-disubstituted alpha-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…More attractively, the transformation of α-imino esters can provide an easy access to various natural and unnatural α-amino acid esters [610]. Up to now, a series of nucleophilic substrates have been reported to react with α-imino esters, such as enamine [1114], carbamate ammonium ylide [15], 1,3-dipolar cycle [16], boronic acid [17], acetylide [18], proparygylic anion [19] and ketene silyl acetal [20].…”
Section: Introductionmentioning
confidence: 99%
“…More attractively, the transformation of α-imino esters can provide an easy access to various natural and unnatural α-amino acid esters [610]. Up to now, a series of nucleophilic substrates have been reported to react with α-imino esters, such as enamine [1114], carbamate ammonium ylide [15], 1,3-dipolar cycle [16], boronic acid [17], acetylide [18], proparygylic anion [19] and ketene silyl acetal [20].…”
Section: Introductionmentioning
confidence: 99%
“…This term was introduced by D. Seebach and E. J. Corey to refer the inversion of reactivity of acyl carbon atoms in their reactions with electrophiles 2 . Analogous methods based on switching the reactivity of amines 3 , imines [4][5][6] , or carbonyl groups [7][8][9][10][11][12][13] have been developed in recent decades. This approach has played a pivotal role in the design of synthetic procedures, allowing access to target molecules that would be difficult to obtain by classical processes.…”
mentioning
confidence: 99%
“…The resultant azlactone products are masked α-amino acids, with hindered α,α-disubstitution patterns that are difficult to achieve via other means. 30 Notably, selective sp 3 C–H activation is observed in benzylic systems, even though Pd(OAc) 2 typically causes arene C–H activation. Further studies to understand the mechanism and, in particular, the role of an observed azlactone dimer on the sp 3 vs sp 2 C–H activation selectivity are underway.…”
mentioning
confidence: 99%